Integrity and rights to gender-affirming healthcare. Issue 11 (30th July 2021) - Rowland, R
Abstract : Gender-affirming healthcare (GAH) interventions are medical or surgical interventions that aim to allow trans and non-binary people to better affirm their gender identity. It has been argued that rights to GAH must be grounded in either a right to be cured of or mitigate an illness—gender dysphoria—or in harm prevention, given the high rates of depression and suicide among trans and non-binary people. However, these grounds of a right to GAH conflict with the prevalent view among theorists, institutions and activists that trans and non-binary people do not have a mental illness and that one can be trans and entitled to GAH without being depressed or suicidal. This paper challenges the orthodoxy that a right to GAH must be grounded in either of these ways and instead argues for a right to GAH grounded in a right to live and act with integrity. The standard view, which this paper explains, is that our rights to live and act with integrity ground a right to religious accommodation in many cases such as a right to not be denied social security due to one's refusal to work a job on a holy day. This paper argues that if our rights to live and act with integrity can ground prima facie rights to religious accommodation, our rights to live and act with integrity ground prima facie rights to GAH.